PCR assay for detection and differentiation of K88ab(1), K88ab(2), K88ac, and K88ad fimbrial adhesins in E. coli strains isolated from diarrheic piglets - Holoda, E; Vu-Khac, H; Andrasková, S; Chomová, Z; Wantrubová, A; Krajnák, M; Pilipcinec, E (Folia microbiologica, 2005)
Primers were designed and prepared and conditions were determined for PCR detection and differentiation of enterotoxigenic E. coli bacterial strains isolated from diarrheic pigs. Primers K88/1 and K88/2 are 25 bp oligomers that correspond to a region of genes encoding one of serological variants of the K88 antigen (K88ab(1), K88ab(2), K88ac or K88ad). A positive result of PCR is an amplificate of 792 bp in size for K88ab and K88ad variant or 786 bp for K88ac variant. The individual serological variants of genes of the K88 antigen could be differentiated by cutting the obtained PCR amplificates by restriction endonucleases. The PCR analysis of 674 E. coli strains isolated from diarrheic pigs showed that 184 strains were K88 positive. By using restriction endonucleases the K88-positive strains were in 4 cases classified as K88ab variant, 180 as K88ac variant and none contained gene for the K88ad variant. Ninety-five % coincidence with serological examination using K88ab, K88ac and K88ad specific antibodies was shown.
Keywords: Animals; Escherichia coli Infections; infekce vyvolané Escherichia coli; antigeny bakteriální; Escherichia coli; polymerázová řetězová reakce; Polymerase Chain Reaction; restrikční enzymy; Slovakia; prasata; Swine Diseases; DNA primery; proteiny z Escherichia coli; průjem; Genetic Variation; nemoci prasat; Swine; Diarrhea; DNA Restriction Enzymes; Antigens, Bacterial; proteiny fimbrií; DNA Primers; Slovenská republika; zvířata; genetická variace; Escherichia coli Proteins; Fimbriae Proteins